محاكاة رمي المدفعية الأرضية مع احتساب تراكم الضرر - الحسن, ميسر; مريم, سليمان (Latakia University Journal -Engineering Sciences Series, 2019)
يمثل قانون التدمير الإحداثي الميزة الاحتمالية الكاملة للأثر التدميري لقذائف المدفعية، وقد أدت صعوبة تحديد هذا القانون إلى البحث عن علاقات أكثر بساطة للتعبير عن هذه الميزة، ولكن ظاهرة "تراكم الضرر"، وقفت عائقاً أمام تبسيطه. في المرحلة الأولى من الدراسة تم وضع نموذج إحصائي، يسمح بمحاكاة عمليات رمي المدفعية والمدفعية الصاروخية على أهداف فردية أو جماعية مختلفة بدون احتساب هذه الظاهرة، مع الاقتصار على معالجة الأهداف المدرعة، كما استخدم هذا النموذج لتقييم فعالية رمي المدفعية الأرضية باعتماد احتمال الإصابة العام كمعيار للفعالية. تعالج هذه الدراسة نفس المسألة مع مراعاة ظاهرة تراكم الضرر، وتعميم نتائج الدراسة على الأنواع المختلفة للأهداف. The law of coordinates destruction represents the full potential advantage of the destructive impact of artillery shells. The difficulty in determining this law has resulted in seeking simplicity for expressing this feature. But the phenomenon of "the accumulation of damage," has proved an impediment to its simplification. At first, a statistical model was built, allowing for the simulation of the shelling operations of artillery and missile artillery of different individual or collective targets without calculating this phenomenon; by only engaging in armored targets, this mode is also used to evaluate the effectiveness of ground artillery shelling by adopting the general hitting possibility as a criterion for effectiveness. This study deals with the same issue, taking into account the phenomenon of the accumulation of damage, and distributing the results of this study to the different types of objectives.